2018
DOI: 10.1111/1460-6984.12400
|View full text |Cite
|
Sign up to set email alerts
|

Technology‐enabled management of communication and swallowing disorders in Parkinson's disease: a systematic scoping review

Abstract: Research evidence supporting technology-enabled management of the communication and swallowing disorders in PD is limited and predominantly low in quality. The treatment of the speech disorder online is the most developed aspect of the technology-enabled management pathway. Future research needs to address technology-enabled management of cognitive-communication and swallowing disorders and the use of a more diverse range of technologies and management approaches to optimize SLT service delivery to people with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 71 publications
(205 reference statements)
3
30
0
12
Order By: Relevance
“…More recently, Internet-based videoconferencing has been used to assess and treat language and motor disorders after brain impairment and Parkinson's disease. A review of studies utilizing Lee Silverman Voice Treatment (a treatment for speech disorders associated with Parkinson's disease) demonstrated that telerehab is feasible through the combination of on-and offline assessments, online clinic visits, and online monitoring of speech or swallowing disorders [41].…”
Section: Usage Of Telerehab To Datementioning
confidence: 99%
“…More recently, Internet-based videoconferencing has been used to assess and treat language and motor disorders after brain impairment and Parkinson's disease. A review of studies utilizing Lee Silverman Voice Treatment (a treatment for speech disorders associated with Parkinson's disease) demonstrated that telerehab is feasible through the combination of on-and offline assessments, online clinic visits, and online monitoring of speech or swallowing disorders [41].…”
Section: Usage Of Telerehab To Datementioning
confidence: 99%
“…Apart from that of cognitive functions, technological implementation for rehabilitation of other clinical manifestations such as speech and language is unfortunately limited. However, communication and swallowing problems, together with hypomimia, are highly prevalent in PD ( 37 ). A limited number of studies with the Lee Silverman Voice Treatment showed benefits on swallowing and reduced parkinsonian hypomimia ( 38 ).…”
Section: Technology-enabled Carementioning
confidence: 99%
“…Individuals with severe and profound disabilities remain largely underserved by the technological revolution [90, 91], despite the evidence that high-tech AAC systems can support language and communication skills for individuals with significant developmental disabilities [57, 92, 93]. Furthermore, relative to the research base focused on children with developmental disabilities, the potential benefits of AAC technologies for adults with acquired disabilities is underexploited [94, 95]. Equally, most of the exciting developments in technology and access methods remain out of the reach of the majority of individuals living with socioeconomic disadvantage [19, 89].…”
Section: The Challenges Of Technological Innovationsmentioning
confidence: 99%